The nature of corruption: An interdisciplinary perspective - Eugen Dimant (Kiel Institute for the World Economy (IfW), 2013)
Corruption has fierce impacts on economic and societal development and is subject to a vast range of institutional, jurisdictional, societal and economic conditions. Research indicates that corruption's predominantly negative effects have arisen to a massive trans-border threat while creating high obstacles to sustainable and prospective development, ultimately impairing everybody's life. This paper provides a comprehensive state-of-the-art survey of existing literature on corruption and its antecedents and effects. Consequently, we bridge the gap between existing theories of different fields of research including economics, psychology, and criminology in order to draw a conclusive picture of corruption on the micro-, meso- and macro-level.
Keywords: D73; F63; H1; O17; K42; 330; Bribery; corruption; development; interdisciplinarity; public economics; survey